Soccer diplomacy : international relations and football since 1914 - Dichter, Heather (Studies in conflict, diplomacy, and peace., 2020)
"Soccer, football, fútbol, Fussball, or voetbal-regardless of how the sport is known locally, it is the universal language to millions of people across the globe. Diplomacy has a similar, if less visible, universal quality. The ubiquity of both soccer and diplomacy have been closely intertwined for decades as many states have sought to use the sport to demonstrate their position within the international community. Even the first FIFA World Cup host, Uruguay, wanted to portray itself as a modern state to the rest of the world and constructed a 90,000-seat stadium and used the event as part of the country's centennial celebrations. Later hosts have sought to use subsequent iterations of this event to project their own messages to the world. South Africa, the home of the 2010 World Cup, used the event to prove it was no longer burdened by its Apartheid past. Soccer's prominence makes it no surprise that FIFA is typically one of the earliest international federations that newly independent countries seek to join. Ghana's independence in 1954 and the country's subsequent application for FIFA membership began a trend that continues today, with South Sudan and Kosovo following in Ghana's footsteps most recently. Even countries such as the United States, Australia, and South Africa, where soccer competes with other sports domestically, attempt to use the global game to their advantage. Soccer has, therefore, enjoyed a long and close relationship with international affairs. In Soccer Diplomacy: International Relations and Football since 1914, editor Heather L. Dichter brings together an international cadre of experts to examine the relationship between soccer and diplomacy. With chapters spanning both temporal and geographical breadth, this volume demonstrates the extent and variety of ways in which soccer has been, and continues to be, used for diplomatic purposes by numerous individuals, organizations, and governments. Chapters explore the historical interactions of soccer in three dimensions: the use of soccer as a tool of nation-state-based diplomacy, soccer as a non-state actor, and the relationship between soccer and diplomatic actors in subnational, national, and transnational contexts. As such the manuscript explores soccer as conduit for representation, communication, and negotiation"--